Marine Molluscs as Indicators of Environmental Change in Glaciated North America and Greenland During the Last 18 000 Years - Dyke, Arthur; Dale, Janis; McNeely, Roger (Géographie physique et Quaternaire, 1996)
ABSTRACTDated mollusc collections are classified in assemblages to map paleo-faunistic zones. Hiatella arctica and Mya truncata account for almost half the records and comprise a restricted arctic assemblage. Arctic assemblages comprise 70% and arctic-dominated assemblages 80% of the database. Fifteen species dominate but 170 taxa are recorded. At last glacial maximum, the arctic zone extended from the Arctic Ocean to the Grand Banks. The boreal zone in the western Atlantic was compressed. The subarctic zone, which today dominates eastern Canada, was small. The boreal zone was extensive in the eastern Pacific where subarctic and arctic zones were compressed. Zones shifted northward during deglaciation and the arctic zone diversified when Bering Strait submerged 10.5-10.3 ka BP. Western Arctic molluscs during Younger Dryas time indicate shallow waters warmer than present. Major North Atlantic currents were established 9.5-9.0 ka BP. The subarctic zone extended to the head of Baffin Bay and a boreal zone became established in West Greenland 9-8 ka BP, with intensive changes about 8.5 ka BP. We relate the latter to the reduction of Mackenzie River discharge and in sea ice export to the North Atlantic as Laurentide ice withdrew from Mackenzie headwaters. The extended subarctic zone in Baffin Bay persisted until 3 ka BP and then retreated about 1000 km on the Canadian side. Boreal-subarctic molluscs in the Gulf of St. Lawrence before 9.5 ka BP derived from the glacial refugium. High boreal-subarctic molluscs farther north probably migrated from Europe. We postulate that the Labrador Current acts as a one-way valve for mollusc migrations at glacial-interglacial scales.